Membrane Proteome of Invasive Retinoblastoma: Differential Proteins and Biomarkers. Issue 5 (13th June 2018) - Danda, Ravikanth; Ganapathy, Kalaivani; Sathe, Gajanan; Madugundu, Anil K.; Krishnan, Uma Maheswari; Khetan, Vikas; Rishi, Pukhraj; Gowda, Harsha; Pandey, Akhilesh; Subramanian, Krishnakumar; Prasad, T. S. Keshava; Elchuri, Sailaja V.
Abstract: Purpose: Retinoblastoma (RB) is a pediatric ocular cancer which is caused due to the aberrations in the RB1 gene. The changes in the membrane proteomics would help in understanding the development of the retinoblastoma and could identify candidates for biomarkers and therapy. Experimental design: Quantitative proteomics is performed on the enriched membrane fractions from pooled normal retina ( n = 5) and pooled retinoblastoma tissues ( n = 5). The proteins are tryptic‐digested and tagged with iTRAQ labels. Orbitrap mass spectrometry is used to analyze and quantify the deregulated membrane proteins involved in the RB tumor progression. Immunohistochemistry (IHC) is used to further validate few of the differentially expressed proteins. Results: A total of 3122 proteins are identified of which, 663 proteins are found to be deregulated with ≥two fold change in the RB tumor compared to the retina. 282 proteins are upregulated and 381 are downregulated with ≥2 peptide identifications. Bioinformatic analysis revealed that, most of the proteins are involved in the transport, cellular communication, and growth. Overexpression of lamin B1 (LMNB1) and transferrin receptor (TFRC) are observed in RB tumors using IHC. Conclusion and clinical relevance: The present study, is the first comprehensive quantitative membrane proteomic atlas of the differentially regulated proteins in RB compared to the retina. LMNB1 and TFRC could be potential biomarkers for this childhood cancer.